Chemical and bromatological characteristics of elephant grass silages with the addition of dried cashew stalk - Rêgo, Margareth Maria Teles; Neiva, José Neuman Miranda; do Rêgo, Aníbal Coutinho [UNESP]; Cândido, Magno José Duarte; de Souza Carneiro, Maria Socorro; Lôbo, Raimundo Nonato Braga (FapUNIFESP (SciELO), 2010)
The objective of this study was to evaluate the nutritive value of elephant grass (Pennisetum purpureum, Schum.) silages with the addition of 0, 4, 8, 12 and 16% dried cashew stalk (Anacardium occidentale L.) - DCS, based on the fresh matter. A randomized complete design with four replications was used. Twenty 210 L plastic drums were used as experimental silos. The levels were determined of the dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose, ether extract (EE), total carbohydrates (TC), non-fibrous carbohydrates (NFC), neutral detergent insoluble nitrogen (NDIN,% total N), acid detergent insoluble nitrogen (ADIN, % total N), pH values, ammonia nitrogen (in percentage of the total nitrogen, N-NH3, % total N), lactic acid, acetic acid, butyric acid and propionic acid. Adding DCS resulted in higher values of DM, CP, EE, NFC, NDIN (% total N), ADIN (% total N), pH, lactic acid and propionic acid. On the other hand, with increasing DCS levels, a linear decline was observed in values of NDF, ADF, hemicellulose, ammonia nitrogen (% total N) and butyric acid. DCS did not show effect on the TC and acetic acid in the silages. As a result, up to 16% dehydrated cashew stalk may be added to elephant-grass silages, based on the fresh matter, to increase CP and NFC levels and decrease NDF and ADF and improve the fermentation patterns. It should be taken into account that higher NDIN and ADIN values may interfere in nitrogen availability and therefore in further DM intake. © 2010 Sociedade Brasileira de Zootecnia.
Características bromatológicas e fermentativas da silagem de capim-elefante com adição do pedúnculo de caju desidratado
Keywords: Anacardium occidentale; Fermentation; Industrial by-products; Nutritive value; Pennisetum purpureum